(untitled) (Torani Journal of Fisheries and Marine Science, 2018)
This study attempted to analyze the distribution and contamination status of heavy metals (Cu, Fe and Zn) along western coast of Bali Strait in Banyuwangi, East Java. Bali Strait is one of the many straits in Indonesia with high fisheries activities that could potentially contributed to high heavy metal pollution. There were five sampling areas from the north to south: Pantai Watu Dodol, Pantai Kalipuro, Ketapang Port, Pantai Boom and Muncar as the fish landing area. Heavy metal pollution in these locations comes from many different activities such as tourism, fish capture and fish industry and also domestic activities. Contamination factor (CF), geo-accumulation index (Igeo) and enrichment factor (EF) of each heavy metal were calculated to obtain contamination status of the research area. The concentrations of Fe were observed the highest (1.5-129.9 mg/kg) followed by Zn (13.2-23.5 mg/kg) and Cu (2.2-7.8 mg/kg). The distribution of Cu, Fe and Zn showed variability among the sampling locations in which high concentrations of Cu and Zn were higher in Ketapang Port, whereas high concentration of Fe was high in almost all sampling locations. According to the pollution index, contamination factors of Cu, Fe and Zn were low (CF < 1 and Igeo < 1). However, high index of EF (> 50) showed high influence of the anthropogenic activities to the contribution of the metals to the environment. This could also because of the high background value used in the calculation of the index due to the difficulties in finding background value from the sampling areas. Keywords: heavy metals, pollution index, contamination factor, geo-accumulation index, Bali Strait